Seeking maternal health care in rural Nigeria: through the lens of negofeminism - Ogochukwu Udenigwe; Friday E. Okonofua; Lorretta F. C. Ntoimo; Sanni Yaya (BMC, 2023)
Abstract Background Feminist scholarship is acutely aware that health is not dependent on behavioural choices alone but on interlocking social determinants that affect people's capacity to lead healthy lives. Women are situated within social structures that impact their health. but there is limited engagement with interpretive tools such as feminist theories that centre the realities of African women, particularly in the context of maternal health. It is imperative that women's control over their reproductive health and autonomy in seeking care, particularly skilled maternal healthcare are understood within this context. This study seeks to examine pregnant women's socio-cultural realities in a Nigerian context and in congruence with articulations of African feminism. Feminist scholarship acknowledges that women are situated within social structures that impact their health. Therefore, this paper seeks to examine pregnant women's socio-cultural realities in a Nigerian context and in congruence with articulations of African feminism. Method This is a cross-sectional qualitative study of a total of 64 participants: 39 women and 25 men in Ewato and Okpekpe communities, two Local Government Areas of Edo State in southern Nigeria. The study presents findings from eight sex-and-age desegregated focus group discussions. This study reports on emergent data related to women's decision-making in accessing skilled maternal care. Data were transcribed and translated to English. Using the NVivo 1.6 software, data were coded and analyzed using a conventional approach to content analysis. Results Findings describe ways in which women negotiate authority by ascribing the role of decision-maker to their men spouses while maintaining influence over their pregnancy healthcare decisions and actions. Negofeminism's concepts of alliance, community and connectedness were highlighted through men's constructive involvement in maternal health. Furthermore, women were shown to maneuver patriarchal norms to gain control of their healthcare decisions. Conclusion This study offers a different narrative from the dominant view of non-Western women, specifically African women, as oppressed passive victims who are ineffectual in taking charge of their health. From the perspective of negofeminism, women navigate patriarchal environments to yield the best possible maternal health outcomes. The current study can be useful in informing policy and programming that acknowledges women's social embeddedness.